2021
DOI: 10.1098/rsob.210125
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib-mediated cell cycle arrest can occur in the absence of the CDK inhibitors p21 and p27

Abstract: The use of CDK4/6 inhibitors in the treatment of a wide range of cancers is an area of ongoing investigation. Despite their increasing clinical use, there is limited understanding of the determinants of sensitivity and resistance to these drugs. Recent data have cast doubt on how CDK4/6 inhibitors arrest proliferation, provoking renewed interest in the role(s) of CDK4/6 in driving cell proliferation. As the use of CDK4/6 inhibitors in cancer therapies becomes more prominent, an understanding of their effect on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…We previously showed that p21 protein starts to increase after two days CDK4/6i treatment (Pennycook and Barr, 2022) and p53, a key transcription factor for p21, was shown to be required for long-term cell cycle arrest after washout of prolonged CDK4/6i treatment (Crozier et al, 2022; Wang et al, 2022). The increase in p21 protein correlates with the loss of the ability of cells to re-enter S-phase after CDK4/6i washout between two and three days of CDK4/6i treatment ( Figure 1E ) and p21 induction is p53-dependent ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that p21 protein starts to increase after two days CDK4/6i treatment (Pennycook and Barr, 2022) and p53, a key transcription factor for p21, was shown to be required for long-term cell cycle arrest after washout of prolonged CDK4/6i treatment (Crozier et al, 2022; Wang et al, 2022). The increase in p21 protein correlates with the loss of the ability of cells to re-enter S-phase after CDK4/6i washout between two and three days of CDK4/6i treatment ( Figure 1E ) and p21 induction is p53-dependent ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been assumed that these agents directly inhibit CDK4/6 enzymatic activity, but this has recently been called into question by work suggesting that by binding to CDK4/6, they in fact operate as indirect CDK2 inhibitors [50]. This claim has, in turn, been refuted by other studies, and it is critical to resolve this issue, the answer to which forms the foundation for all research using these compounds [103]. Indeed, the CDK2 inhibition hypothesis is built upon the notion that CDK4/6 activity requires the formation of trimers which also contain cyclin D and p21/p27, a concept which is also controversial [103][104][105][106].…”
Section: Future Directions and Unanswered Questionsmentioning
confidence: 99%
“…This claim has, in turn, been refuted by other studies, and it is critical to resolve this issue, the answer to which forms the foundation for all research using these compounds [103]. Indeed, the CDK2 inhibition hypothesis is built upon the notion that CDK4/6 activity requires the formation of trimers which also contain cyclin D and p21/p27, a concept which is also controversial [103][104][105][106].…”
Section: Future Directions and Unanswered Questionsmentioning
confidence: 99%
“…Also, p21 levels were not affected by palbociclib monotherapy or after combination therapy, while other studies in which higher palbociclib concentrations were applied, detected upregulation of p21 (35,36). However, a recent study demonstrated that the CDKinhibitors p21 and p27 are not required for palbociclibmediated cell cycle arrest (39).…”
Section: Discussionmentioning
confidence: 85%